Los plazos de prescripción y la Administración Pública (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2014)
This paper draws your attention to the statute of limitation (prescription). Sometimes it can be confusing who is responsable for claiming the debt. Administration must also be as equally attentive to the deadlines given. The deadlines of limitation can be unclear because of legislations changing and a loop hole in the law may be found in some individual cases that may allow an extension to the general 4 year rule.
Keywords: Limitation or prescription; deadline or terms, inactivity; complaint; debts; contractors; administration; taxes